MSTO1 is a cytoplasmic pro‐mitochondrial fusion protein, whose mutation induces myopathy and ataxia in humans. Issue 7 (29th May 2017) - Gal, Aniko; Balicza, Peter; Weaver, David; Naghdi, Shamim; Joseph, Suresh K; Várnai, Péter; Gyuris, Tibor; Horváth, Attila; Nagy, Laszlo; Seifert, Erin L; Molnar, Maria Judit; Hajnóczky, György
Abstract: The protein MSTO1 has been localized to mitochondria and linked to mitochondrial morphology, but its specific role has remained unclear. We identified a c.22G > A (p.Val8Met) mutation of MSTO1 in patients with minor physical abnormalities, myopathy, ataxia, and neurodevelopmental impairments. Lactate stress test and myopathological results suggest mitochondrial dysfunction. In patient fibroblasts, MSTO1 mRNA and protein abundance are decreased, mitochondria display fragmentation, aggregation, and decreased network continuity and fusion activity. These characteristics can be reversed by genetic rescue. Short‐term silencing of MSTO1 in HeLa cells reproduced the impairment of mitochondrial morphology and dynamics observed in the fibroblasts without damaging bioenergetics. At variance with a previous report, we find MSTO1 to be localized in the cytoplasmic area with limited colocalization with mitochondria. MSTO1 interacts with the fusion machinery as a soluble factor at the cytoplasm‐mitochondrial outer membrane interface. After plasma membrane permeabilization, MSTO1 is released from the cells. Thus, an MSTO1 loss‐of‐function mutation is associated with a human disorder showing mitochondrial involvement. MSTO1 likely has a physiologically relevant role in mitochondrial morphogenesis by supporting mitochondrial fusion. Synopsis: MSTO1 has been localized to mitochondria and linked to their morphology but its role remained unclear. Here, an MSTO1 loss‐of‐function mutation is shown to be associated with a human disorder showing mitochondrial involvement. Mutation of MSTO1 is documented in a family of patients with multisystem disease. MSTO1‐deficient patient cells and HeLa cells show impaired mitochondrial morphology and fusion that can be rescued by MSTO1 overexpression. MSTO1 is a soluble cytoplasmic protein that likely interacts with the mitochondrial fusion proteins. Abstract : MSTO1 has been localized to mitochondria and linked to their morphology but its role remained unclear. Here, an MSTO1 loss‐of‐function mutation is shown to be associated with a human disorder showing mitochondrial involvement.